Pengelolaan Kurikulum Terintegrasi di SMP An-Naja Boarding School Bandung Barat - Abdul Muhyi Alawiy Athallah (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
Integrated Curriculum is a curriculum composed to carry out a holistic education. Unfortunately, the implementation of an integrated curriculum still found some obstacles that hamper achieving the goal of the curriculum itself. Therefore, the school should manage the integrated curriculum as well. This study aims to describe the management of the integrated curriculum in SMP An-Naja Boarding School West Bandung through planning, implementing, and evaluating the curriculum. This study uses a qualitative approach with a descriptive method. The data sources were selected purposively, and snowball sampling. The Data collection is conducted through interviews and documentation. Data analysis uses data reduction techniques, data presentation, and drawing conclusions. Then to check the validity of the data, the authors use triangulation techniques. The result of the study in SMP An-Naja Boarding School West Bandung shows that the management of an integrated curriculum is done well enough. Therefore, the explanations are as follows: 1) planning of integrated curriculum is done by determining the curriculum objectives and arranging the organization of curriculum contents. 2) Implementing the integrated curriculum is done by implementing curriculum programs and supervision. 3) Evaluation of integrated curriculum is done by an educational system evaluation model that contains input, process, and products.